2009
DOI: 10.1073/pnas.0806516106
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal neuroimaging provides a highly consistent picture of energy metabolism, validating 31 P MRS for measuring brain ATP synthesis

Abstract: Neuroimaging methods have considerably developed over the last decades and offer various noninvasive approaches for measuring cerebral metabolic fluxes connected to energy metabolism, including PET and magnetic resonance spectroscopy (MRS). Among these methods, 31 P MRS has the particularity and advantage to directly measure cerebral ATP synthesis without injection of labeled precursor. However, this approach is methodologically challenging, and further validation studies are required to establish 31 P MRS as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 58 publications
(88 reference statements)
5
43
1
1
Order By: Relevance
“…Consequently, pH values measured in our study are likely to represent intracellular pH, under physiological as well as under pathological conditions. Recent in vivo MRS data suggest that a large majority of brain Pi is located in neurons as opposed to glial cells, based on the fact that Pi is in a compartment where oxidative metabolism strongly dominates glycolytic metabolism (Chaumeil et al, 2009;Lei et al, 2003). Altogether, these observations allow us to interpret our results as an increase in neuronal pH in HD.…”
Section: Arguments For Intracellular Neuronal Ph Increasesupporting
confidence: 63%
“…Consequently, pH values measured in our study are likely to represent intracellular pH, under physiological as well as under pathological conditions. Recent in vivo MRS data suggest that a large majority of brain Pi is located in neurons as opposed to glial cells, based on the fact that Pi is in a compartment where oxidative metabolism strongly dominates glycolytic metabolism (Chaumeil et al, 2009;Lei et al, 2003). Altogether, these observations allow us to interpret our results as an increase in neuronal pH in HD.…”
Section: Arguments For Intracellular Neuronal Ph Increasesupporting
confidence: 63%
“…V TCA values derived from experimental 13 C-glutamate data using either the simplified or the complete model appear to be identical, taking SD into account, and consistent with the values we usually report (4)(5)(6)(7). Results are summarized in Table 2.…”
Section: Accuracy and Robustness Of The Simplified Modelsupporting
confidence: 81%
“…Two macaque monkeys (Mac1 and Mac2) were fasted overnight and anesthetized by continuous intravenous propofol infusion. Glucose infusion was performed according to a protocol that has been extensively validated and used in our laboratory (4)(5)(6)(7). It started with a 3-min bolus of 99% enriched uniformly labeled glucose ([U-13 C 6 ]glucose) to reach a 3-fold increased glycemia.…”
Section: Acquisition Of Experimental Time Coursesmentioning
confidence: 99%
“…2 Furthermore, saturation transfer experiments can be used to quantify reaction rates between exchanging pools 3 and can be of particular interest when studying brain metabolism together with other methods. 4 At high magnetic fields, there is an increase in 31 P spectral resolution that can help differentiate peaks that would otherwise overlap. Previous studies in the muscle have reported resonances between 5.1 and 5.3 ppm that could be attributed to a second pool of Pi (the main pool resonating at 4.9 ppm).…”
Section: Introductionmentioning
confidence: 99%